UPAYA MEMFASILITASI KEMAMPUAN MEMECAHKAN MASALAH DAN KESADARAN LINGKUNGAN SISWA SMA MELALUI PEMBELAJARAN SETS - Rahmawati, Dina (2017)
This research conducted to identify efforts facilitate troubleshooting and senior high school students environmental awareness through learning SETS. The research method is weak experiment, with the design of the study "The One-Group Pretest-Posttest Design". The subject of research as much as 34 sophomores X. Effect learning SETS to students' ability to solve problems are analyzed based on one sample z test scores and students of environmental awareness was analyzed by test score Wilcoxon using the calculation statistical program SPSS 24.0 for Windows. Instruments used in this research is to test the ability to solve the problem on the concept of Pollution and Environmental Protection, in the form of an essay as many as 15 questions, and the attitude scale questionnaire of 20 questions. The analysis showed that the SETS can enhance problem-solving skills and environmental awareness of students and learning SETS significant effect on the ability to solve problems and environmental awareness of students. In addition, students' creativity in finding out pretty good waste management by creating products that are aesthetically pleasing.---- Penelitian ini bertujuan untuk mengidentifikasi upaya memfasilitasi pemecahan masalah dan kesadaran lingkungan siswa SMA melalui pembelajaran SETS. Metode penelitian adalah weak experiment, dengan desain penelitian "The One-Group Pretest-Postest Design". Subyek penelitian sebanyak 34 siswa SMA kelas X. Pengaruh pembelajaran SETS terhadap kemampuan memecahkan masalah siswa dianalisis berdasarkan skor uji z satu sampel dan kesadaran lingkungan siswa dianalisis berdasarkan skor uji Wilcoxon dengan menggunakan program penghitungan statistic SPSS 24.0 for Windows. Instrumen yang digunakan dalam penelitian ini adalah tes kemampuan memecahkan masalah pada konsep Pencemaran dan Pelestarian Lingkungan Hidup, berupa essay sebanyak 15 soal, dan angket skala sikap sebanyak 20 pertanyaan. Hasil analisis menunjukkan bahwa SETS dapat meningkatkan kemampuan memecahkan masalah dan kesadaran lingkungan siswa dan pembelajaran SETS berpengaruh signifikan terhadap kemampuan memecahkan masalah dan kesadaran lingkungan siswa. Disamping itu, kreativitas siswa dalam menemukan pengolahan limbah tahu cukup baik dengan membuat produk-produk yang bernilai estetik.